The aftermath of COVID-19 pandemic on the diagnosis of TB at a tertiary care hospital in India - Druti Hazra; Kiran Chawla; Vishnu P. Shenoy; Akhilesh K. Pandey; Nayana S (Elsevier, 2021)
Background: The recent COVID-19 pandemic became a looming catastrophe over global public health and severely disrupted essential healthcare services like tuberculosis (TB). This study estimated the impact of the COVID-19 in the diagnosis of TB, a microbiology laboratory-based overview. Method: This ambispective observational study was conducted at the Department of Microbiology in a tertiary care hospital in South Karnataka from January 2019 to December 2020. A standardized data collection sheet was prepared to collect the month-wise total number of suspected TB and confirmed TB samples. Data were analyzed using EZR 3.4.3 (R, open-source). Categorical variables were expressed in frequency and percentage. The Chi-square test was performed to test the difference in proportions and p < 0.05 indicated statistical significance. Results: In this study, a significant drop was observed in suspected TB specimens in 2020 compared to 2019, i.e. 54.8% for microscopy, along with 34.2% and 49.7% for Xpert MTB/RIF and MGIT culture respectively. Also, a sharp decline in confirmed TB samples was noted in 2020 with 49%, 43.8%, and 59.7% reduction with microscopy, Xpert MTB/RIF, and MGIT culture respectively, compared to 2019. Another major finding from this study reveals the PTB: EPTB proportion changed from 2.7:1 in 2019 to 2.1:1 in 2020, divulging an overall increase in EPTB sample proportion in 2020 (p = 0.0385). Conclusion: The COVID-19 pandemic adversely impacted the TB diagnostic services, resulting in a significant reduction of active TB case detection. It highlights an urgent need to revise the strategies to control and eliminate TB in this hour of the pandemic crisis.